Recognizing Elder Abuse: An Interprofessional Simulation Experience With Prelicensure Health Care Students. Issue 4 (October 2020) - Cunningham, Shala; Cunningham, Cynthia; Foote, Lisa
Abstract : Background and Purpose: A common role within all health care professions includes the ability to recognize and report elder abuse. However, teaching the characteristics and assessment of abuse can be difficult. To allow students to engage in a realistic case-based scenario within a health care team, an immersive simulation was developed involving the care of an elderly woman with signs of abuse. The purpose of this quasiexperimental study was to explore the influence of the experience on the participants' perceptions of interprofessional care and their understanding of the assessment of abuse. Methods: This study utilized a mixed-methods research design. A sample of convenience of nursing and physical therapy students (n = 143) from 3 institutions in southwest Virginia was utilized for this study. Participants' perceptions were assessed using the Interprofessional Socialization and Valuing Scale (ISVS) and through focus group interviews. Results: Students demonstrated a statistically significant improvement based on the Wilcoxon matched pairs test ( P < .001) on all 21 questions of the ISVS. A phenomenological study design was employed for qualitative analysis of focus group interviews performed postsimulation to generate information about the students' perceptions of the experience. Two themes emerged from the interviews: (1) communication as a team to provide wholistic patient care and (2) recognition of abuse. Discussion: The students reported an improved understanding of collaboration on a health care team and how to investigate potential abuse occurring in the home. This further supports research suggesting the importance of interactive learning techniques in teaching health care students to recognize symptoms of elder abuse.